Short-term outcomes of a novel endoscopic clipping device for closure of the internal opening in 100 anorectal fistulas - Proßt, Rüdiger Lothar; Joos, Andreas (Techniques in coloproctology, 2016)
BackgroundOne hundred consecutive applications of a new clipping device, the OTSC® Proctology (Ovesco Endoscopy AG), were analyzed to assess its efficacy for the treatment of complex anorectal fistulas.MethodsIn patients with anorectal fistulas, minimally invasive surgery with the OTSC® Proctology system was performed according to a standardized technique: the fistula tract was debrided using a special fistula brush, and the clip was applied on the internal fistula opening. In some of the patients, postoperative pain was evaluated using a visual analog scale. After 6 months, the postoperative clinical course and the fistula healing were assessed.ResultsA total of 100 OTSC® Proctology procedures were performed in 96 patients with 55 transsphincteric, 38 suprasphincteric, 2 extrasphincteric, and 5 rectovaginal fistulas. In all but 11 fistulas (8 Crohn’s disease, 3 ulcerative colitis), the fistulas were of cryptoglandular origin. The median operation time was 32 min (range 17-66 min). There were no major intraoperative technical problems. All patients found the postoperative pain to be tolerable with standard pain medication. The short-term results of 99 clip applications were analyzed: the healing rate for first-line fistula therapy was 79 %, whereas in recurrent fistulas, the success rate was 26 %. OTSC® Proctology was successful in 45 % of fistulas associated with inflammatory bowel disease and in 20 % of rectovaginal fistulas.ConclusionsOTSC® Proctology provides convincing results as first-line treatment for complex cryptoglandular fistulas. It is a safe, effective, minimally invasive, and sphincter-sparing procedure with postoperative pain comparable to other types of fistula surgery.